(untitled) (International relations and international law Journal, 2016)
Іn this article, the author considers problems about restriction of political rights of civil servants in Kazakhstan. He analyzes the limitations stipulated in the Law on Civil Service of 23 July 1999 and the Code of honor of civil servants approved by the Decree of the Republic of Kazakhstan President dated May 3, 2005 №1567 concludes incorrectness of certain provisions of these documents. As well as the author notes the contradiction requirements of certain provisions «memo to employees of public authorities and institutions with state participation by using the Internet, including social networks and blog platforms», approved by acting Minister for Investment and Development of the Republic of Kazakhstan Zh. Kasymbekov with the Constitution and ratified by our state International Covenant on Civil and political Rights. Taking into consideration some norms of memo unreasonably restrict political rights of civil servants author proposes to exclude them.